Зовнішня торгівля суб’єктів господарювання Закарпатської області - Рубіш, М. А. (Видавництво Львівської політехніки, 2016)
Проаналізовано сучасний стан зовнішньої торгівлі товарами та послугами Закарпатської області, виявлено основні тенденції зовнішньої торгівлі. Здійснено аналіз географічної структури експорту та імпорту товарів та послуг, відповідно до якого були зроблені висновки щодо основних партнерів серед країн–членів ЄС, які межують із Закарпатською областю, та інших країн світу. Визначено основні частки структури експорту та імпорту товарів та послуг Закарпатської області за досліджуваний період. One of the areas of effective cooperation and the development of our country along with its regions is using one of the important forms of international economic relations – foreign trade. The integration of economy of the country (region) in global processes have a positive impact on their development as a whole, provide the use of existing natural resources and competitive advantages, it promotes socio-economic development. On the example of Transcarpathia region there have been made an important analysis on regions’ foreign trade as a whole. Foreign trade of goods and services is an important part of foreign trade activities of Transcarpathia region and requires continuous implementation of measures to stimulate it. The aim of this work is to identify the main trends of international trade in the region on the example of Transcarpathia region, determining geographical structure and analyzing the trade balance. In article author has analyzed value of exports and imports in the years 2010–2014, has ascertained preference of imports over exports, indicating that the region is dependent on imports: comparing 2010 and 2014, we observe their growth, but if you analyze the share of exports and imports in region’s total foreign trade, they remain virtually unchanged. According to the reduced geographical structure, enterprises of Transcarpathia region have been exporting mostly to Europe, due to its geographical location. Most of the enterprises of Transcarpathia region export machinery, equipment, machinery and electrical equipment (63.9 % of total in 2014), and textile materials and products (9.5 %). The largest importers of goods and services to the Transcarpathia region are Europe, CIS and Asia. Regarding the volume of goods’ import, there is a tendency to its growth. The balance of foreign trade for the period of 2010–2014 years – negative, although decreased by half compared with 2013. Over the period the bulk of services imports were from the following countries: Italy, Germany, Poland, Romania and Hungary. In 2014 a decrease of the share services from the Russian Federation, the United Kingdom, Slovakia, Hungary and the Czech Republic were observed. The balance of services for the years 2010–2014 is positive in contrast to the net balance of goods. The results obtained during conducted by us studies give reason to believe that Transcarpathia should use its advantage – relevance to the borders and intensify cross-border trade. The border regions play a specific role in implementing the leading trends of global development, namely in foreign economic activity, including foreign trade liberalization and a sharp increase in cross-border trade, intensification of interstate movement of population. In the region continuously carried out work on the study of markets and the search for foreign partners for mutually beneficial cooperation mechanisms with the aim to improve country's exports and overcome the negative trends in foreign trade. The Further research require management tools of economic processes in the region, that ensure the use of foreign trade advantages of the Transcarpathian region after full ratification of the Association Agreement Ukraine and the EU.
Business entities foreign trade in Transcarpathia region
Keywords: зовнішньоекономічна діяльність; зовнішня торгівля; експорт; імпорт; зовнішньоторговельне сальдо; суб’єкти господарювання; структура товарів та послуг; international business; foreign trade; export; import; foreign trade balance; businesses; structure of goods and services